2008
DOI: 10.1002/ejoc.200701104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Tripodal Scaffold for Solid Phase Synthesis of Artificial Receptors

Abstract: A convergent synthesis for the preparation of a new orthogonally protected tripodal scaffold has been developed. The scaffold was successfully coupled to a Tentagel solid support and further derivatised at the three attachment points demonstrating its possible use for combinatorial chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…ninhydrin. If the amidation/esterification is complete, the Fmoc group can be released by piperidine and quantitatively detected by a well established UV measurement [322]. This in turn will give reliable data for initial -NH 2 /-OH loading (amount of a functional group on a resin generally expressed as mmol/g) of the resin.…”
Section: Chemical Analysismentioning
confidence: 99%
“…ninhydrin. If the amidation/esterification is complete, the Fmoc group can be released by piperidine and quantitatively detected by a well established UV measurement [322]. This in turn will give reliable data for initial -NH 2 /-OH loading (amount of a functional group on a resin generally expressed as mmol/g) of the resin.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Recently, Madder et al have also shown that despite the flexibility of the scaffold, the arms are organized in a parallel way providing a very good preorganization [19]. The synthesis is depicted in Scheme 2.…”
Section: Synthesis Of Amphiphilic Iron Chelators Based On Catechol Grmentioning
confidence: 99%
“…It was not a surprise to notice that the primary amine functions are not compatible with the aldehyde in (19): cyclisation readily occurred to produce the very stable bicyclic aminal (20) in 70% yield (Scheme 4a), but it was quite unexpected to notice that the nitrogen atom of amides (21) were also still enough nucleophilic to react similarly with the -CHO group (see Fig. (4b)).…”
Section: Synthesis Of Amphiphilic Iron Chelators Based On Catechol Grmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] We then evaluated whether this transformation could take place in growth media. Using 20 µM [Cp*Ru(cod)Cl] ( 2 ) as a catalyst in PABA-free M9 glycerol minimal medium at 37 °C, we were able to detect formation of PABA from 100 µM 1 (Table 1, Entry 1).…”
mentioning
confidence: 99%